Philosophy and educational policy : a critical introduction - Winch, Christopher (RoutledgeFalmer, 2004)
This book is designed to provide an up-to-date introduction to the Philosophy of Education. It addresses many of the 'traditional' topics in the field, as well as more contemporary policy issues in education.